(untitled) (Sudurpaschim Spectrum, 2026)
This study undertakes a bibliometric analysis of digital marketing literature, focusing on consumer preferences and decision-making patterns from 2010 to April 2024. As digital technologies continue to reshape marketing strategies, this study investigates the influence of advancements in artificial intelligence (AI), big data, and personalized approaches on consumer behavior and preferences. The primary objective is to identify emerging research trends, key contributors, and significant areas of interest in the digital marketing field. Analyzing data from Scopus and Web of Science, 6,220 documents were reviewed to assess research growth, collaboration trends, and thematic changes. The findings reveal an increasing emphasis on marketing strategies driven by artificial intelligence, user generated content, and influencer marketing, with a pronounced focus on personalized customer experiences and interactions on social media platforms. This study highlights the growing importance of consumer preferences and international collaborations in digital marketing research while emphasizing the need for further investigation into digital marketing practices in developing economies. This study contributes to understanding the evolving dynamics in digital marketing by offering a comprehensive review of scholarly contributions in the field. This study provides significant gaps in the current literature, advocating for future research to address challenges related to ethical considerations, technological advancements, and regional variations in digital marketing adoption.